PENGARUH BELANJA PEMERINTAH DAN INVESTASI TERHADAP TINGKAT PARTISIPASI ANGKATAN KERJA DI INDONESIA - Ainun Anugrawati; Iwang, Baso (ICOR: Journal of Regional Economics, 2024)
The labor force participation rate is the percentage of the labor force with a population of working age. The higher the labor force participation rate, the greater the share of the working age population that is actually involved, or trying to be involved, in productive activities, namely producing goods and services, with a certain period of time. The purpose of this study was to determine the effect of government spending and investment on the level of labor force participation. This type of research is quantitative using multiple linear regression with the research location is Indonesia. Using secondary time series data obtained from the central statistics agency, foreign investment and other sources, the methods of collection are documentation and acces to internet sites. The result of this study indicate that the direct expenditure variable (X1) has a positive and significant effect on the labor force participation rate (Y), the indirect expenditure variable (X2) has a positive and significant effect on the labor force participation rate (Y), and investment (X3) has a positive and significant impact on the labor force participation rate (Y). Keywords: direct shopping, indirect shopping, Investment, labor force participation rate.